Highly regioselective C4-hydrazinylation of 2,4-dichloroquinolines: expedient synthesis of aminoquinoline substituted pyrrolidin-2,5-diones via hydrazinylquinolines - Kumar, Gopal Senthil; Zeller, Matthias; Gonnade, Rajesh Ghanshyam; Prasad, Kamam Jayarampillai Rajendra (Tetrahedron Letters, 2014)
A new class of hydrazinylquinoline regio-isomers has been synthesized through SNAr reaction of 2,4-dichloroquinolines with hydrazine hydrate. The reaction stops at the mono-substitution product with high regioselectivity at the C-4 rather than C-2 position of dichloroquinolines. The hydrazinylquinolines were subsequently converted into aminoquinoline substituted pyrrolidin-2,5-diones in the presence of Eaton's reagent. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 5-diones; Eaton's reagent; Hydrazinylquinolines; Pyrrolidin-2; Regioisomers; SNAr reaction

Spirochromone-chalcone conjugates as antitubercular agents: synthesis, bio evaluation and molecular modeling studies - Mujahid, Mohammad; Perumal, Yogeeswari; Sriram, D.; Basavanag, U. M. V.; Dıaz-Cervantes, Erik; Cordoba-Bahena, Luis; Robles, Juvencio; Gonnade, Rajesh Ghanshyam; Karthikeyan, Muthukumarasamy; Vyas, Renu; Krishnan, M. Muthu (RSC Advances, 2015)
A new series of spirochromone annulated chalcone conjugates were synthesized and evaluated for their antitubercular activity against Mycobacterium tuberculosis H37Rv strain. These compounds were subjected to molecular modeling studies using docking and chemoinformatics based approaches. The docking simulations were performed against a range of known receptors for chalcone derived compounds to reveal MTB phosphotyrosine phosphatase B [MtbPtpB] protein as the most probable target based on the high binding affinity scores. Five compounds exhibit significant inhibition, showing minimum inhibitory concentration values i.e. MIC values ranging from 3.13–12.5 μg mL−1. Further analysis of the synthesized compounds with known and in-house developed chemoinformatics tools unequivocally established their potential as anti-tubercular compounds. QSAR modeling revealed a quantitative relationship between biological activities and frontier molecular orbital energies of synthesized compounds. The predictive model can be employed further for virtual screening of new compounds in this series.

Enantioselective synthesis of spiro γ-butyrolactones by N-heterocyclic carbene (NHC)-catalyzed formal [3+2] annulation of enals with 3-hydroxy oxindoles - Mukherjee, Subrata; Joseph, Sumi; Bhunia, Anup; Gonnade, Rajesh Ghanshyam; Reddy, Santhi Vardhan; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2017)
The N-heterocyclic carbene (NHC)-catalyzed enantioselective formal [3 + 2] annulation of α,β-unsaturated aldehydes with 3-hydroxy oxindoles is presented. Under oxidative conditions using the bisquinone oxidant, the reaction resulted in the synthesis of spiro γ-butyrolactones in moderate to good yields, enantioselectivity and diastereoselectivity. The reaction likely proceeds via the generation of the NHC-bound α,β-unsaturated acylazolium intermediate from enals, which was intercepted by the dioxindoles in a formal [3 + 2] pathway to form the spirocyclic compounds. However, a deeper mechanistic investigation revealed that the reaction can also proceed via the homoenolate intermediate. In this case, the dioxindole was oxidized to the corresponding isatin derivative using traces of air under basic conditions, and was intercepted with the NHC-bound homoenolate intermediate in a formal [3 + 2] pathway to afford the spiro compound.

Exploring the gem-dimethyl effect in the formation of imine-based macrocycles and cages - Madhu, Suresh; Rashmi, E. V.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2017)
Using the gem-dimethyl effect as a platform, a variety of organic [2+2] macrocycles and [2+3] cofacial cages was obtained in high yields. Imine-based macrocyclization could be performed even at high concentrations (0.5 to 1.0 M), via instant mixing of aldehydes and amines.

General nickel-catalyzed method for C-H bond alkynylation of heteroarenes through chelation assistance - Punji, Benudhar; Khake, Shrikant manmathappa; Soni, Vineeta; Gonnade, Rajesh Ghanshyam (Chemistry - A European Journal, 2017)
A general nickel-catalyzed method for the alkynylation of heteroarenes through monodentate chelation assistance is described. Many heterocycles, including indoles, pyrroles, imidazoles and pyrazole, efficiently coupled with (triisopropylsilyl)alkynyl bromide, and synthetically important functional groups, such as halides, ether, nitrile, nitro were tolerated. Synthetic applicability of this Ni-catalyzed method is demonstrated by the removal of triisopropylsilyl (-SiiPr₃) group, and further functionalization into triazolyl, benzofuranyl and alkynyl arene derivatives. Preliminary mechanistic investigations on the alkynylation of indole suggest that the reaction proceeds through kinetically relevant C-H activation and follows the two-electron redox pathway. A catalytically competent Ni-species, [(Phen)₃Ni].NiBr₄ has been isolated and structurally characterized.

N - heterocyclic - carbene - catalyzed umpolung of imines - Patra, Atanu; Mukherjee, Subrata; Das, Tamal Kanti; Jain, Shailja; Gonnade, Rajesh Ghanshyam; Biju, Akkattu T. (Angewandte Chemie International Edition, 2017)
N-Heterocyclic carbene (NHC) catalysis has been widely used for the umpolung of aldehydes, and recently for the umpolung of Michael acceptors. Described herein is the umpolung of aldimines catalyzed by NHCs, and the reaction likely proceeds via aza-Breslow intermediates. The NHC-catalyzed intramolecular cyclization of aldimines bearing a Michael acceptor resulted in the formation of biologically important 2-(hetero)aryl indole 3-acetic-acid derivatives in moderate to good yields. The carbene generated from the bicyclic triazolium salt was found to be efficient for this transformation.

Structural insights into the hydrogen-bonding and folding pattern in ant-ant-pro-gly tetrapeptides - Baravkar, Sachin B.; Kotmale, Amol S.; Mobin, Samir R.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2017)
In this paper, we provide structural insights into the hydrogen-bonding and folding pattern in Ant-Ant-Pro-Gly tetrapeptides (Ant: anthranilic acid; Pro: proline; and Gly: glycine). Comparison of the C-terminal esters and their amide analogs revealed strikingly different H-bonding networks. Whereas the ester analogs displayed an open structure without terminal H-bonding interactions, the amide analogs showed a completely folded structure. Structural details were revealed by using a combination of X-ray crystal structure studies and NOE-based molecular dynamics (MD) simulation studies.

Synthesis of annulated bis-indoles through Au(I)/brønsted acid-catalyzed reactions of (1H-indol-3-yl)(aryl)methanols with 2-(arylethynyl)-1H-indoles - Patil, Nitin T.; Inamdar, Suleman M.; Gonnade, Rajesh Ghanshyam (Organic & Biomolecular Chemistry, 2017)
A general method to access annulated bis-indoles from (1H-indol-3-yl)(aryl)methanols and 2-(arylethynyl)-1H-indoles under the catalysis of the Ph3PAuOTf/Brønsted acid binary catalyst system has been developed. The reaction was found to proceed in a highly efficient manner and benefit from easy-to-make starting materials, broad substrate scope and operational simplicity. The potential of this method has also been exemplified for the synthesis of pyrrole-annulated indoles using 2-(phenylethynyl)-1H-indoles and phenyl(1H-pyrrol-2-yl)methanols. Furthermore, the use of a ternary catalyst system, involving PdCl2/Brønsted acid/Ph3PAuOTf catalysts, has been realized for the synthesis of annulated bis-indoles starting directly from 2-(phenylbuta-1,3-diyn-1-yl)aniline and (1H-indol-3-yl)(aryl)methanol. Mechanistically, this reaction is very interesting since the overall process involves three different catalytic cycles catalyzed by three different catalysts in a relay fashion.